Pengaruh Tingkat Persediaan Terhadap Rentabilitas Ekonomi Pada PT Sepatu Bata, Tbk - Popon Rabia Adawia; Ayu Azizah (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2019)
This study examines the effect of inventory levels on economic rentability at PT Sepatu Bata Tbk. Referring to two variables, namely economic rentability as the dependent variable / dependent variable (x) and inventory level as independent variables / independent variables (y). The purpose of this research is to find out whether or not there is a positive and significant influence between inventory level rotation, economic profitability at PT Sepatu Bata Tbk, and to find out how much influence the inventory level has on economic rentability. The research method used in carrying out this research is an associative research method which aims to determine the influence of the two variables studied. This study uses simple linear regression data analysis techniques, while for the hypothesis test statistical tests are carried out with the T test. For the regression equation obtained is Y = 18.72 - 0.23X. This study concludes that the inventory does not significantly influence the economic rentability of PT Sepatu Bata Tbk. These results can be seen from tcount of -1.585 and ttable of 2.015, which means that tcount is smaller than ttable. While the influence of inventory variables on economic rentability is 33.4% while the remaining 66.6% is influenced by other variables outside of this study. Keywords: Inventory, economic rentability, profitability.